2008
DOI: 10.1093/jac/dkn234
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of genetic diversity and drug resistance mutations in HIV-1 among untreated patients from Mali between 2005 and 2006

Abstract: HIV-1 genetic diversity seems increased in Mali, but the overall HIV-1 primary resistance prevalence remains low. This is consistent with the findings from other West African countries where prevalence rates are lower than 5%. However, considering the large scaling up of ARV use in this country, it is necessary to regularly monitor the development of primary resistance in Mali.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
31
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 26 publications
(19 reference statements)
6
31
2
Order By: Relevance
“…No significant difference between 2005 and 2006 in www.intechopen.com the prevalence of primary resistance of different classes of antiretroviral drugs has been observed. A similar study of treatment-naive patients recently showed a higher prevalence of primary resistance (9.9%) than was previously reported by Derache and colleagues Derache, 2008). So also have other studies reported late failures to drug treatment in Mali and in Burkina Faso with median treatment duration lasting 18 months (Sylla, 2008).…”
Section: Hiv Drug Resistance In Malisupporting
confidence: 63%
See 2 more Smart Citations
“…No significant difference between 2005 and 2006 in www.intechopen.com the prevalence of primary resistance of different classes of antiretroviral drugs has been observed. A similar study of treatment-naive patients recently showed a higher prevalence of primary resistance (9.9%) than was previously reported by Derache and colleagues Derache, 2008). So also have other studies reported late failures to drug treatment in Mali and in Burkina Faso with median treatment duration lasting 18 months (Sylla, 2008).…”
Section: Hiv Drug Resistance In Malisupporting
confidence: 63%
“…Currently 9 subtypes have been identified worldwide in the HIV-1 group M (A, B, C, D, F, G, H, J and K). Viruses E and I in the envelope are recombinant strains (Peeters, 1999 (Derache, 2008). A second recombinant strain was CRF06_cpx with 19.5% and 11% infections respectively occurring in the same period.…”
Section: Circulating Recombinants Forms Of Hiv In Malimentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that these non-B subtypes may have natural polymorphisms described as ETR RAMs (5,14). Although ETR previously showed comparable activities against different group M subtypes (A to H), including several CRFs, the testing was done with few strains, and few data concerning the impact of the HIV-1 subtype on the virological response to ETR are currently available (1,24).…”
mentioning
confidence: 99%
“…In this subtype, there is an intrinsic difficulty in synthesizing pol-A homopolymeric sequences that leads to template pausing at codon 65, facilitating the acquisition of K65R under selective drug pressure (Coutsinos et al, 2010;Coutsinos et al, 2009). The natural polymorphisms found in the RT of treatment-naive patients (10% in 726 patients) infected with HIV-1 non-B subtypes had no significant impact on susceptibility to ETR (Cotte et al, 2009;Derache et al, 2008;Maiga et al, 2010).…”
Section: Impact Of Hiv-1 Diversity In Drug Resistancementioning
confidence: 94%